A História nas histórias em quadrinhos : o uso da Graphic Novel Maus na aprendizagem histórica - Oliveira, Jhuan Cláudio Matos de (2020)
The historical learning process has been the focus of researchers for contemplating the changes brought about by the cultural profusion of the 21st century. With the advent of the Google Age advocated by Carlos Ginzburg and the mass culture of Umberto Eco, the steady growth in multimedia consumption by young students is noticeable. In this sense, this dissertation analyzes the ways to use the graphic novel produced by Art Spiegelman, Maus: The Story of a Survivor, in the process of historical learning by means of graphic narratives present in comics. This dissertation also establishes the textual and aesthetic specificities of comics, demarcating their space as a source for history as well as their contribution to historical learning. Consequently, Rüsen's theory of Historical Consciousness, articulated with the research field of History Education, aided by the concept of historical empathy, provides the theoretical and methodological apparatus necessary for the elaboration of a didactic intervention proposal in the format of a workshop class for the final years of elementary school II.